The formation of iron aluminides on aluminum surface by using a Q-switched Nd:YAG laser - Bidin, Noriah (2013)
The formation and growth of Fe based aluminum diffusion layers at the Fe-Al interface have been investigated to improve the surface hardness. The diffusion of Fe into Al has been accomplished by focusing a Q-switched Nd:YAG laser on the modified surface. The variety of the layer depth is achieved based on the type of heating and quenching media. Microstructural characterization and mechanical properties of the modified surface were carried out via gas discharge spectrometer GDS, X-Ray diffraction (XRD), Scanning electron microscope (SEM), and Vickers Hardness tester. The results indicate that hardness at the interface of Fe-Al layer is increased. The optimum hardness achieved as 93 HV at corresponding critical energy density of 438 Jcm-2.